Frequency, Causes and Findings of Brain Computed Tomography Scan at University of Lahore Teaching Hospital: Frequency, Causes and Findings of Brain Computed Tomography Scan - Akhtar, Hadia; Yousaf Farooq, Syed Muhammad; Shan, Ali; Naeem, Muhammad; Azhar, Ayesha; Sajid Dar, Sawaira; Fayyaz, Zainab; Amjad, Esha; Fatima, Arooj; Muhammad Noor, Hafsa (Pakistan Journal of Health Sciences, 2022)
Cranial computed tomography (CT) is the most generally utilized diagnostic method for the emergent evaluation of head trauma (TBIs) because it is readily accessible, quick, and sensitive for clinically relevant traumatic brain injuries as well as non-traumatic abnormalities. Objective: To determine the frequency, causes, and findings of brain computed tomography scan at The University of Lahore teaching hospital. Methods: A descriptive study was conducted at The University of Lahore Teaching Hospital. A sample of 202 brain CT scans from a total of 933 participants seen in the CT department was obtained using a suitable sampling technique. Data analysis was done using SPSS version 21.0. Results: There were 78 (38.6%) female patients and 124 (61.4%) male patients out of 202 total patients. The mean age of the patients was 47.1± 23 years. The most prevalent of them, brain atrophy, was observed in 63 (31.2%) of the patients. 51 (25.2%) patients had infarction, 36 (17.8%) had sinusitis, 24 (11.9%) had ischemic demyelination, and 16 (7.9%) had fractures and hemorrhages. In 8 (4.0%) patients, mastoiditis, tumors, and carcinoma were reported. 7 patients (3.5%) had cysts, 6 patients (3.0%) reported contusions, and 2 patients (1.0%) had abscesses. Conclusions: According to our research, the vast majority of individuals who underwent CT scans had a history of headache and falls and the most frequent observation in the patients was brain atrophy. Other major findings found were sinusitis and infarction.